Diversifying Islamic Haven Assets - Bayu Adi Nugroho (Journal of Islamic Monetary Economics and Finance, 2025)
This study reassesses the safe haven properties of gold and Sukuk using a new framework that incorporates nonstationary volatility and proposes a trading strategy to construct a gold – Sukuk – Islamic equities portfolio that can outperform the hard-to-beat naïve method and the covariance-based approaches. In line with previous studies, it employs data of four exchange-traded funds: Dow Jones Global Sukuk, Wahed FTSE USA Shariah, MSCI Emerging Market Islamic, and SPDR Gold. In the study, an enhanced version of wavelet quintile correlation is proposed to re-evaluate the haven qualities of gold and Sukuk. The results show that gold and Sukuk are safe haven assets. Next, applying a dual momentum strategy, we demonstrate that the risk-adjusted returns of our proposed trading strategy outshine the naïve method and the covariance-based approaches. Our research employs real returns and a rolling window approach to avoid money illusion, overfitting, look-ahead bias, and flawless hindsight. The main results prevail in the robustness tests.